Quality Control Analysis of Black Tea Raw Ingredients (Camellia sinensis) PT ABC - Haryadi, Hari; Iftinaan, Atika Tsuroya (Journal of Agri-Food Science and Technology, 2022)
One of the companies that produce black tea in Indonesia is PT ABC. In PT ABC, the processing system Orthodox Rotorvane produces black tea powder according to market demand, which has a small particle size (broken tea) and quick brewing by applying SNI 01-1902-2016 as a reference for production activities and monitoring the production process. This study contribution to investigate the quality of tea leaf shoots used as production raw materials, especially in the flow of raw material handling, the quality control of raw materials, and the value of the proportion of damage to raw materials. The method used is an analysis based on data Tops Not Eligible/Pucuk Tidak Memenuhi Syarat (PTMS) obtained from each plantation block. The output results obtained show that the value of the proportion of damage to raw materials is still within the control limits where there are only one of the six plantation blocks, namely the Kembang plantation block, produces a value of the proportion of damage outside the control limits with the main factors causing it from human factors, equipment, raw materials and working method used. This research contributes to knowing the value of the proportion of shoot damage for each plantation block at PT ABC.